(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The objective of this work was to study the normal musculotendinousstructures of the ostrich foot. Materials and methods: Ten African apparent healthy adult female ostriches (Struthiocamelus) were slaughtered, and the pelvic limbs were separated from the ankle joint. The different biomedical scanning techniques including radiography, computed tomography (CT), magnetic resonance imaging, and ultrasonography were achieved. Then, the ostrich feet were freshly dissected. Results: The radiographs and CT images showed the bony components of the ostrich foot that revealed the presence of long tarsometatarsus and phalanges of the only developed third and fourth toes. The third digit was the longest and possessed four phalanges, whereas the shorter fourth toe contained five phalanges. The ostrich foot consisted mainly of tendons in addition to several small associated muscles. The extensor structures were the extensor digitorum longus tendon, Mm. extensor propriusdigiti III, and extensor brevis digiti III and IV. On the other hand, the flexor structures were the flexor digitorum longus, flexor hallucis longus, flexor perforansetperforatusdigiti III, and flexor perforatusdigiti III and IV tendons. Furthermore, fibularis longus tendon and two muscles (Mm. abductor digiti IV and lumbricalis) were related to the flexor tendons. Conclusion: The combination between the dissecting anatomy and the different biomedical scanning techniques was of value in describing the normal anatomical course of the musculotendinous structures of the ostrich foot, which aids in the diagnosis of any clinical abnormalities in these structures. Adv. Vet. Anim. Res., 7(2): 242-252, June 2020